Assessment and Management of Post-Intubation Airway Injuries. (March 2017) - Jones, Teresa S.; Sullivan, Andrew; Damle, Sagar; Weyant, Michael J.; Mitchell, John D.; Weitzel, Nathaen S.; Meguid, Robert A.
Tracheal laceration is a known complication of endotracheal intubation. This rare complication remains a diagnostic and management challenge for today's practitioners. This clinical challenge report highlights current surgical and anesthetic management strategies.